Fish Biodiversity in the Swamp Ecosystem of Barumun River Area - Khairul Khairul; Khairul Khairul (Hasanuddin University, 2020)
Swamp flooded is a habitat of various types of fish, which as an feeding ground, shelter, and reproduction. Diversity of fish types has been utilized by the people to catch fish, as a material of consumption and economic income. One of the flooded swamp that people have utilized in the Barumun River area. The purpose of this research is to know the biodiversity of fish in the swamp flooded Barumun River. This research is explorative, with the determination of observation stations with purposive sampling methods. Fish are captured using hand cast fishing nets, fishing rods, and gill nets. Fish are identified using relevant books. Total fishing catches during the study amounted to 298 individuals consisting of 13 genera and 17 speisies. The average value of the Keanakaragaman index is 1,85 with a low cathedral. The average value of uniformity index (E ') is 0,67 in medium category. The average value of the Dominancy index (C) is 0,027 in low category. Based on the results of the study concluded the waters of Rawa Sungai Barumun has suffered disruption due to land function and pollution. This is evidenced by the Oil Palm Factory PT. Nubika Jaya and palm plantations area.